The Influence of People, Process, and Physical Evidence on Word of Mouth Through Customer Satisfaction at Hotel Lafayette Yogyakarta - Teresa Avilla Kasigit; Innocentius Bernarto (Dinasti Review, 2025)
The hospitality industry has shown significant recovery in the aftermath of the COVID-19 pandemic, accompanied by increasingly intense competition, particularly in cultural tourism destinations such as Yogyakarta. Hotel Lafayette Yogyakarta, a four-star hotel with a strong digital reputation, continues to face challenges in achieving its customer satisfaction targets. This study aims to analyze the influence of People, Process, and Physical Evidence on Word of Mouth (WoM), with Customer Satisfaction as a mediating variable. Using a quantitative approach, primary data were collected from 333 respondents who had stayed at Hotel Lafayette Yogyakarta within the last three months. Hypothesis testing was conducted using Structural Equation Modeling (SEM) with SmartPLS 4.1.2 software. The results show that all three elements People, Process, and Physical Evidence have a positive influence on both Customer Satisfaction and Word of Mouth, either directly or indirectly through Customer Satisfaction. Moreover, Customer Satisfaction itsel has a significant positive impact on Word of Mouth. These findings contribute theoretically to the service marketing literature, particularly in the hospitality industry context, and offer strategic recommendations for hotel management to improve customer satisfaction to drive Word of Mouth as a strategy for achieving competitive advantage.